Adidas equity research - an underperforming giant - Lopes, Miguel Nuno Costa Trabulo Campos (2022)
This Work Project presents an equity research of the sporting goods giant, adidas. The main goal is to provide an in-depth analysis of the main factors that will influence adidas in the long-term such as the current pandemic which the world is experiencing and provide a valuation for the end of 2022using different methodologies. The effectiveness of the vaccine, as well as the appearance of new variants will determine the future of the industry. In this way, the recommend position is to “BUY” with an expect share price of €308 for December 2022.